(3GdGYJHGQ aj GdfGSN hGdefShN ef GdBKGQs - (3CHh HcQ Rjf GdOjf eMeO Hf ehSi Hf YKeGf Hf MGRe GdMGRej, GdMGRej,J (B584 (3g` s
(3ChdgG (B:s
(3GdMeO ddg CeG HYO , agPG cJGH CPcQ ajg eG EfJgJ Edi eYQaJg ef fGSN MOjK QShd Gddg Udi Gddg Ydjg hSde hefShNg , EP gh Yde Ldjd s
(3BNQgG (B:s
(3bhdg (B: (3MJi fgGge aGfJghG hbO Tcd Ydi HYV GdfGS GdLeY Hjf gPG GdMOjK hGdMOjK GdBNQ ai GdhGaO GdPi bOe hbGd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3GdfSNI HgG MhGTs
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3fSNI efbhdI Yf fSNI cJHgG dfaSg WGgQ Hf jMji Hf CHj GdNjQ GdYeQGfi SfI (B563 (3g` s
(3Ydi MhGTjgG JUMjMGJ hebGHdGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B117s
Keywords: (3GdMOjK h GdeUWdMs